MULTI-OBJECTIVE ROBUST DESIGN OF ULTRA-HIGH PERFORMANCE CONCRETE GUARDRAIL BASED ON TOPOLOGY OPTIMIZATION - CHEN Peng; LEI ZhengBao (Jixie qiangdu)
The standard guardrail was topologically optimized in the longitudinal stretch direction, the optimal force transmission path was obtained, and the initial section of the new type guardrail was extracted. Then, ultra-high performance concrete material was applied to the collision analysis using the guardrail-vehicle coupling finite element model verified by the actual vehicle experiment. In order to obtain the optimal section parameters that minimize the acceleration of vehicle centroid and the maximum dynamic displacement of guardrail, taguchi method combined with physical programming method was used for multi-objective robust design considering the influence of uncertain factors. Finally, the simulation results of the optimized guardrail and the standard guardrail are compared, and the results show that the crashworthiness of the optimized new guardrail can be comprehensively improved. The work has practical engineering significance.